Digital Inclusion as a Core Component of Social Inclusion - Reisdorf, Bianca; Rhinesmith, Colin (Social Inclusion, 2020)
There is a large body of research that has examined digital inequities, inequalities, and divides—i.e., those countries, communities, and individuals digitally left behind or disadvantaged. Whereas we know quite a lot about what is lacking and for whom, there is less focus on what works to alleviate these inequalities and divides in a variety of cultural contexts. This thematic issue brings together scholarship on digital inclusion initiatives and research from over 20 countries and in the context of numerous aspects, including different types of initiatives as well as different types of target audiences for these initiatives. Each article provides unique insights into what does and does not work in various communities, making recommendations on what could be done to improve the examined initiatives. We hope that the breadth and depth of articles presented here will be useful not just for academic audiences seeking to broaden their understanding of digital inclusion and ‘what can be done’ rather than focusing on ‘what is amiss,’ but also for policymakers and digital inclusion initiatives who are eager to expand and advance their digital inclusion work within their communities.